Occupational Safety and Health Risk Analysis for Chainsaw Operators in Logging Operations at PT. XY, Riau Province - Hutasuhut, Ika Lestari (Jurnal Penelitian Kehutanan BONITA, 2025)
Logging activities in Industrial Plantation Forests (HTI) still rely on chainsaws as semi-mechanical tools, combined with mechanical equipment such as harvesters. The use of chainsaws provides efficiency in the production process but also poses high risks to occupational safety and health (OSH) for chainsaw operators. This condition requires a comprehensive risk analysis to protect chainsaw operators from work hazards that may lead to fatal incidents. This study aims to analyze the level of OSH risk among chainsaw operators during logging activities at PT. XY, Riau Province. The method employed is HIRACH (Hazard Identification, Risk Assessment, and Control of Hazards), using a field observation approach, in-depth interviews, questionnaire distribution to ten chainsaw operators, and triangulation with secondary data to strengthen result validity. The results show that 23 types of hazards and 28 risks were identified, originating from environmental, mechanical, biological, and chemical factors. Most risks fall into the moderate category (79%), such as risks from steep terrain, extreme weather, and the presence of wild animals. Meanwhile, 21% of the risks are categorized as high, particularly those related to chainsaw operation, including chain breakage, kickback, excessive vibration, and noise levels exceeding safe limits. The study concludes that risk control must follow the hierarchy of control, including elimination, substitution, engineering control, administrative control, and the use of personal protective equipment (PPE). The implementation of a comprehensive OSH management system, supported by continuous training and intensive supervision, is essential to reduce the potential for accidents and occupational diseases, while also supporting productivity and the sustainability of forest harvesting activities.